ANALISIS STRATEGI PENGEMBANGAN BMT (BAITUL MAAL WAT TAMWIL) DI KOTA MEDAN - Isma Ilmi Hayati Ginting; Ilyda Sudardjat (Departemen Ekonomi Pembangunan USU, 2014)
This study aims to identified internal and external factors of BMT in Medan and making the business strategy that can be applied to developed BMT in Medan.The data that used in this study was primary data that has been collected using questionnaire and benn analyzed using internal and external factor analysis also SWOT quantitative analysis, SWOT is the stands for Strenghts, Weakness, Opportunity, and Threats, SWOT stages assumes the effective strategy that maximize strengths and opportunities and minimalyzed weaknesses and threats.The strategy that been obtained was a. Developing bookkeeping system that appropriate with sharia system and more transparent with the sharing system; b. Utilize government support against Islamic banking with increasing the types of sharia products; c. Government support can be used to fix the information and technology that used to give the good services to the community; d. Creating partnership with other bank that doing Islamic principles to do the training and development program for the human resource on BMT Amanah Ray in Medan; e. Holding counseling for the community about sharia system on BMT dan bookkeeping system that BMT Amanah Ray owned to open the peoples insight about BMT Amanah Ray in Medan and also promoting it; f. Increase the role of BMT trough the soft credit policy with mild condition; g. Promotion about BMT that impose sharia bookkeeping systems; h. Fix the facilities and infrastructures on technology to compete with another institutions.Keywords : Strategy, BMT, SWOT, Internal Factor, External Factor.